Analysis of the Behavior of Household Contacts TB Patients in Providing Tuberculosis Prevention Therapy (TPT) at The Work Area Sri Padang Public Health Center Tebing City in 2024 - Feridani Simarmata, Aida; Wasliati, Balqis; Aprinawaty Sirait, Reni (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Around 3.5-10% of people who come into contact with TB patients will be infected but will not get TB, of which 5-10% are likely to get TB in their lifetime. Research is needed on the provision of Tuberculosis Prevention Therapy (TPT) to household contacts of TB patients considering that all TB patients found have received treatment. This study is a qualitative study using a descriptive research design where researchers investigate carefully to obtain more in-depth information about the description of the behavior of household contacts of TB patients in providing tuberculosis prevention therapy (TPT) in the work area of ??the Sri Padang Health Center, Tebing Tinggi City. The research variables are knowledge, attitudes, beliefs, and family support. The results of the study are good knowledge will help them undergo preventive therapy with more discipline; An attitude of alertness and caution towards the risk of TB transmission in household contacts shows a good understanding of the dangers of TB disease; Strong belief in various aspects related to TPT, including its effectiveness, support from health workers, and safety of therapy, is very important to ensure that household contacts of TB patients can undergo TPT successfully and effectively; and family play an important role in the decision to undergo or not undergo TPT. The suggestion is that the level of knowledge of household contacts about TPT still needs to be improved, trust, provision of clear information about the side effects of the drug.